Double Scanning in the Diagnosis of Lung Tumours - Vándor, F. C.; Szekulesz, A.; Szabó, I. (Nuklearmedizin - NuclearMedicine, 1972)
In the localization of lung tumours radioisotope investigations provide highly revealing data concerning indications for surgery and radiotherapy. Joint use of perfusion lung scintigraphy and radioactive chlomerodrin scanning of the data obtained more reliable.